2016
DOI: 10.1002/2015ja021920
|View full text |Cite
|
Sign up to set email alerts
|

Local time asymmetries and toroidal field line resonances: Global magnetospheric modeling in SWMF

Abstract: We present evidence of resonant wave‐wave coupling via toroidal field line resonance (FLR) signatures in the Space Weather Modeling Framework's (SWMF) global, terrestrial magnetospheric model in one simulation driven by a synthetic upstream solar wind with embedded broadband dynamic pressure fluctuations. Using in situ, stationary point measurements of the radial electric field along the 1500 LT meridian, we show that SWMF reproduces a multiharmonic, continuous distribution of FLRs exemplified by 180° phase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…They recently extended this work to consider the inclusion of a plasmasphere in their model, which still resulted in significant, albeit reduced, resonant excitation (Claudepierre et al, 2016). In a similar manner, Ellington et al (2016) also showed significant resonance excitation within a global simulation. Degeling et al (2010) considered a compressed dipole model of the magnetosphere again displaying the prevalence of FLR excitation in 3-D.…”
Section: 1002/2017ja025018mentioning
confidence: 87%
“…They recently extended this work to consider the inclusion of a plasmasphere in their model, which still resulted in significant, albeit reduced, resonant excitation (Claudepierre et al, 2016). In a similar manner, Ellington et al (2016) also showed significant resonance excitation within a global simulation. Degeling et al (2010) considered a compressed dipole model of the magnetosphere again displaying the prevalence of FLR excitation in 3-D.…”
Section: 1002/2017ja025018mentioning
confidence: 87%
“…What is now clear is that plumes connect the equatorial F region ionosphere to the dayside magnetopause and the nightside magnetotail plasma sheet (e.g., Su et al, 2001a, b;Horvath and Lovell, 2011;Walsh et al, 2014a, b;Foster et al, 2014). Through the formation and evolution of the different plumes, they impact wave generation and wave-particle interactions (e.g., Summers et al, 2008;Chen et al, 2012;Halford et al, 2015), particle precipitation (Spasojević and Fuselier, 2009;Yuan et al, 2011Yuan et al, , 2013, ion outflow (e.g., Zeng and Horowitz, 2008;Tu et al, 2007), local-time asymmetries in ULF wave field-line resonance (FLR) signatures (e.g., Archer et al, 2015;Ellington et al, 2016), satellite communication and navigation systems (Ledvina et al, 2004;Basu et al, 2005;Datta-Barua et al, 2014), and even the coupling efficiency of the solar wind to the magnetosphere (Borovsky and Denton, 2006;Borovsky et al, 2013;Ouellette et al, 2016;Fuselier et al, 2016). Though we now have a new appreciation and understanding of plumes, there are still many unanswered questions on their formation (e.g., Kelley et al, 2004;Horvath and Lovell, 2011;Zou et al, 2013Zou et al, , 2014Borovsky et al, 2014) and impact on global magnetospheric dynamics McFadden et al 2008;Walsh et al, 2014Walsh et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The technique requires the presence of a broadband source as described above to excite the field lines at each station at their local eigenfrequency (Menk et al, 2004;Waters et al, 1991). Claudepierre et al (2010), Ellington et al (2016), and Elsden and Wright (2018) have all shown that such a broadband source can be used to excite field lines using simulations. Many studies have utilized the cross-phase technique to study magnetospheric ultralow frequency (ULF) waves (e.g., Clausen et al, 2008;Kawano et al, 2002;Sandhu et al, 2018;Waters et al, 1995).…”
Section: Introductionmentioning
confidence: 99%